Comparative study of the Roma population Romania vs Spain - Mocanu, Dorina; Chirugu, Gianina (Technium Social Sciences Journal, 2024)
A comparative study of the Roma population in Romania and Spain can provide a detailed insight into the different aspects of the life of these communities in the two countries. This research could be conceived using a mixed approach, combining qualitative and quantitative methods to obtain a comprehensive and contextualized image.